Improvement of the method of drilling and blasting operations at the use of explosive substance «Ukrainite» in underground mining works - Stupnik, Mykola; Kalinichenko, Vsevolod; Rymarchuk, Boris; Pysmennyi, Serhii; Fedko, Mykhailo; Kalinichenko, Elena (Technology audit and production reserves, 2018)
The object of research is a rock massif of iron ore, which is destroyed by an explosive located in deep wells. One of the most problematic places is ensuring uniform grinding of the rock massif during underground mining of mineral deposits at great depths. In the Kryvyi Rih iron ore basin (Kryvyi Rih, Ukraine) in underground mining let’s use the Ukrainian-made Grammonite 79/21 explosive, which provided an opportunity to obtain high-quality grinding of the ore mass to a depth of 1200 m. With a decrease in mining, these indicators deteriorate significantly, due to the manifestations of rock pressure, which leads to the overcoming of wells and increased specific charge for blasting. A comprehensive method is used based on an analysis of existing methods that affect the specific charge of an explosive. According to practice data, it is found that when using an emulsion explosive in mining operations, the specific consumption of an explosive decreases, while the cost of extraction decreases and the quality of grinding of the massif improves. However, due to the lack of a methodology for calculating the parameters of drilling and blasting operations, the «Ukrainite PP-1» emulsion explosive is not widely used. The development of the methodology taking into account the characteristics of the «Ukrainite PP-1» emulsion explosive will improve the extraction of ore mass. It is shown that the use of «Ukrainite PP-1» emulsion explosive leads to a decrease in the total length of wells by 35 %, and a decrease in production costs. This is due to the fact that the proposed method of calculation has the peculiarity of taking into account the specific costs of emulsion explosives obtained by pilot tests, in particular, the efficiency coefficient of emulsion explosives. Due to this, the costs of drilling and blasting work are reduced and it is possible to obtain a calculated economic effect from the introduction of this technology at the level of 0.6 c. u./t. The proposed pattern of drilling the massif by the downward fans, compared with similar known, can reduce the time for drilling and improve the grinding of the rock massif without changing technology.